2015
DOI: 10.1016/j.colsurfa.2014.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Foam improved oil recovery: Foam front displacement in the presence of slumping

Abstract: This version is available at https://strathprints.strath.ac.uk/52032/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…Previous studies in the case of homogeneous permeability [11,13,14] have demonstrated that the system attains a state in which the 'apparent' horizontal velocity is uniform with position. 'Apparent' horizontal velocity is the difference in horizontal displacement per difference in time between two points on the front at the same vertical height at two different times.…”
Section: Modifying Velocity For Concavities and Regridding The Frontmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in the case of homogeneous permeability [11,13,14] have demonstrated that the system attains a state in which the 'apparent' horizontal velocity is uniform with position. 'Apparent' horizontal velocity is the difference in horizontal displacement per difference in time between two points on the front at the same vertical height at two different times.…”
Section: Modifying Velocity For Concavities and Regridding The Frontmentioning
confidence: 99%
“…The two additional cases, mentioned above i.e. increase in driving pressure and surfactant slumping, use a suitable modification of the same model [13,14]. Therefore, in a similar fashion, we propose some changes to the original pressure-driven growth model that will make it appropriate to describe the case of the heterogeneous reservoir.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is fortunate because the equations governing pressure-driven growth are well behaved in the case of convex shapes, whereas to handle concave shapes [5], special strategies need to be put in place for solving the equations. Unfortunately there are a number of scenarios (generalisations of the simple homogeneous, isotropic, unit driving pressure case that is discussed above) for which the foam front will no longer be convex, instead concavities will appear [5,8]. Amongst these is the case of a sudden rise in the driving pressure which is what is considered here.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilized foams have been used for enhanced oil/gas recovery (EOR) [11][12][13][14], the remediation of non-aqueous phase liquids (NAPLs) [15][16][17], and CO 2 geological storage [18,19]. The stabilized CO 2 -water foam can be used for geological CO 2 sequestration and CO 2 -enhanced oil recovery.…”
Section: Introductionmentioning
confidence: 99%